2010
DOI: 10.1142/s1793042110002995
|View full text |Cite
|
Sign up to set email alerts
|

Motivic Double Shuffle

Abstract: The goal of this paper is to give an elementary proof of the double shuffle relations directly for the Goncharov and Manin motivic multiple zeta values. The shuffle relation is straightforward, but for the stuffle, we use a modification of a method first introduced by Cartier for the purpose of proving stuffle for the real multiple zeta values. We will use both the representation of multiple zeta values on the moduli spaces of curve introduced by Goncharov and Manin and we will apply suitable blow-up sequences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 7 publications
0
18
0
1
Order By: Relevance
“…In this paper all the dual vector space means compact dual (linear functional whose support is finite dimension). Since motivic multiple zeta values satisfy double shuffle relations [16], [19], [21]. Any statement holds for the classical multiple zeta values which is deduced only by double shuffle relations also holds for the motivic multiple zeta values.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…In this paper all the dual vector space means compact dual (linear functional whose support is finite dimension). Since motivic multiple zeta values satisfy double shuffle relations [16], [19], [21]. Any statement holds for the classical multiple zeta values which is deduced only by double shuffle relations also holds for the motivic multiple zeta values.…”
Section: Introductionmentioning
confidence: 93%
“…It's easy to show that gr D r A odd = gr D r A for r = 1, 2 from the results of [5], [11], [21]. The motivic Broadhurst-Kreimer conjecture (Conjecture 1.1) and its uneven part conjecture (Conjecture 1.2) suggest that gr D r A odd = gr D r A should also hold for r = 3.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…[18], but also [12], [16], [13], [8]), Goncharov (and co-authors) defined motivic multiple zeta values, which are (framed) mixed Tate motives with the motivic version ζ m (2) of ζ(2) being zero, and which form a Hopf algebra denoted MZ under the tensor product, with a coproduct defined explicitly by Goncharov ([13], foreshadowed by [12]). It is known that the motivic multiple zeta values satisfy relations (7.4)-(7.5) (see [13], for (7.5) see also [24]). Furthermore, F. Brown defined [4] a graded algebra comodule of motivic multiple zeta values H in which ζ m (2) is non-zero, and showed that H is non-canonically isomorphic to MZ ⊗ Q[ζ m (2)] and that Goncharov's period map (with values in a quotient of R only) can be lifted to a surjection H → → Z.…”
Section: 3mentioning
confidence: 99%
“…This certainly occurs experimentally up to n = 9. The paper [19] by I. Soudères takes up this question in the context of motivic multiple zeta values.…”
Section: The Algebra Of Cell-zeta Valuesmentioning
confidence: 99%